2017
DOI: 10.5530/pj.2017.4.77
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Acute Oral Toxicity Study of White Tea Leaf (Camellia sinensis (L.) Kuntze) Ethanolic Extracts

Abstract: Background: White tea is a kind of tea which manufactured with minimal processing only drying without fermentation process. White tea prepared from very young tea leaves or buds of Camellia sinensis (L.) Kuntze, Theaceae, covered with tiny, silvery hairs, and dried immediately after picking to prevent oxidation and commonly used as a beverage and herbal medicine. Objective: The present study was aimed to evaluate the safety of the white tea leaf ethanolic extract (WTE) with acute toxicity tests. Methods: The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In this study, there were no significance differences in body weight gain with control group in the result analysis in p≥0.05. This concurs with the acute oral toxicity evaluation study by Saleem et al (2017) and Ardiana et al (2017), who reported that animals administered with Saccharum munja and Camellia sinensis extract respectively, had normal body weight gain and food and fluid intake for 14 days 20,21 . In this study, no lesions or changes in colour for both the control and treated groups were found during macroscopic observation of organs.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, there were no significance differences in body weight gain with control group in the result analysis in p≥0.05. This concurs with the acute oral toxicity evaluation study by Saleem et al (2017) and Ardiana et al (2017), who reported that animals administered with Saccharum munja and Camellia sinensis extract respectively, had normal body weight gain and food and fluid intake for 14 days 20,21 . In this study, no lesions or changes in colour for both the control and treated groups were found during macroscopic observation of organs.…”
Section: Discussionsupporting
confidence: 90%
“…This is due to the biosynthesis and accumulation of phytoconstituents at different region of the plant parts and toxic specificity of the compounds against the selected cell lines. The traditional practitioners of this area orally administered the stem bark extract to cure liver diseases (Jaundice), diarrhea and dysentery [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] it was also noticed that the patients did not show any symptoms of irritability and behavior patterns such as tremors, salivation, and diarrhea. To authenticate the nontoxic effect of BEE acute toxicity experiment was conducted on albino rats.…”
Section: Discussionmentioning
confidence: 99%
“…17 The liver and kidney tissues were washed with normal saline and fixed immediately in 10% formaldehyde buffer for a period of 18 h. The tissues were dehydrated in graded (50-100%) ethanol, followed by washing with xylene. Paraffin (56-58ºC) embedding was done at 58 ± 1ºC for 4 h and sections of 5 μm were taken using a rotary microtome.…”
Section: Histopathological Studymentioning
confidence: 99%
“…This clearly indicates that CS-AgNPs possess significant antidiabetic activity compared to a previous study that used a normal C. sinensis extract in the same streptozotocininduced mice model. [49] The variation in efficacy can be attributed to the ability of CS-AgNPs to release C. sinensis phytochemicals specifically at the target site in diabetic mice. Additionally, lipid profile and creatinine tests were performed to further confirm the antidiabetic activity.…”
Section: Antidiabetic Activitymentioning
confidence: 99%